Bibliography on access to plant genetic resources and intellectual property rights - Libreros, D.; International Plant Genetic Resources Institute (2002)
Plant genetic resources constitute the biological foundation of humankind. Research systems and agricultural production also depend on them. Plant genetic resources result from natural evolution and human intervention, and are considered patrimony of the nations. Although their conservation, use and exchange are among the objectives of the Convention of Biological Diversity and have been recognized internationally, the threats against their safety continue to increase. This bibliography, which contains work published all over the world since 1984, intends to contribute to IPGRI's goal on plant genetic resources policy. It contains 433 references with local descriptors. The records are organized in 2 subjects-access to plant genetic resources (91) and intellectual property rights (342). It includes references on the status of intellectual property rights in several countries, the application of farmers' rights to local varieties and the consequences of limiting access in the development of seed production systems. Available in electronic form only as a Portable Document Format (PDF) file.